Aggregation and adsorption behavior of low concentration aqueous solutions of hexadecyltrimethylammonium ortho, meta, and parafluorobenzoate - Landázuri, G. (2012)
The aggregation properties of 2-, 3-, and 4-fluorobenzoic acids (2FBA, 3FBA, and 4FBA, respectively) and their salts with hexadecyltrimethylammonium cations (HTA2FB, HTA3FB, and HTA4FB) in water were studied with a battery of techniques. Their activity at the air/solution interface has been also studied. The position of the fluorine atom in the acid affected the solubility, adsorption, and aggregation in the pure acids solutions. The 4FBA is less water soluble, more hydrophobic, and has the lower critical aggregation concentration of the three isomers. The behavior of the HTA2FB compound in aqueous solution is different from that of HTA3FB and HTA4FB. The critical micelle concentration, critical concentration for sphere-to-rod-like micelle transition, and Krafft point of HTA3FB and HTA4FB are lower than those of the other surfactant but their surface activities are higher. The differences between the HTA2FB and the other two surfactants have been explained on the basis of the regular solution theory of mixed micelles and in light of the analysis of the hydration shell of the acids through molecular dynamic simulations. The results of the present work suggest that the different behaviors are due to a combination of different dehydration tendencies and the steric possibility of inclusion of the counterions in the micelle palisade layer. The formation of rod-like micelles by HTA2FB, while the tetradecyltrimethylammonium 2-fluorobenzoate only forms spherical aggregates, is explained on the basis of the packing parameter. The mentioned factors are complementary to others presented in literature. These conditions may be used in the rational design of micelles by means of molecular dynamics simulations, reducing the trial-and-error approach used to date.